Penerapan Konsep Pembelajaran Berbasis Kecerdasan Majemuk (Multiple Intelligence) pada Anak Usia Dini - A. Tabiin (Edukasia Islamika : Jurnal Pendidikan Islam, 2017)
Early childhood education is very important and basic. In this step the parents should be really pay attention for their children education. In choosing education institution as well as choosing to teach their children by themself at home. In early childhood education should pay attention about their children intelligency, besause among one child to another is different. The parents as well as the teacher should identify their children intelligency in order to give direction and develop their intelligency maximally. In this decade, a children said to be intelligence is masterinh mathematic or science., and actually there are many children are not mastering this two aspects, those are mathematic and science become frustated to compete the achevement. in fact, the are so many update development appear relate to someone's intelligency and there are many facts about many succeed people is not always comparable with mathematic and science competence.The intelligency nowadays is not only viewed from two aspect competences above, but also is categorized in many kinds of intelligencies such as stated by Howard Gardner.